The effects of physical exercises in the morning and evening time on some physiological parameters - Al-temimi, Shatha Q.; Kadhem, Hanaa S.; Thuwaini, Mahdi M. (University of Thi-Qar Journal, 2019)
The present study aimed to compare the effect of physical exercise in the morning and evening time on some physiological parameters which comprised from renal function test including blood urea nitrogen (BUN), serum creatinine (S.cr), some of serum electrolyte. (sodium and potassium) and blood pressure. The study included (20) males students volunteers of the second stage - College of Physical Education - University of Basra (10) students from the morning group and (10) students from the evening group. The results Showed that The Bun and S.cr concentration post-exercise in morning and evening group are significant higher than Pre-exercise in the same time, the Bun., S.cr concentration post-exercise in the evening group are higher than post-exercise in morning group (p?0.05). But no significant (P?0.05) in Sodium and Potassium . While the SYS and DIS blood Pressure level post-exercise are significant lower than Pre-exercise in the morning and evening group, and found that the SYS and DIS blood Pressure post-exercise in evening group are lower In comparison with post-exercise in morning group (p?0.05). Conclusion: The physical exercise cause significantly higher in Bun and S.cr, the concentration of Bun and S.cr post-exercise in evening time are higher than post-exercise in morning time, no significant was appeared in sodium and potassium levels. Conversely, significantly lower in SYS and DIS blood Pressure post-exercise.While, SYS and DIS blood Pressure post-exercise in evening time are significant lower In comparison with post-exercise in morning time